KONFIGURASI UUD 1945 DAN AMANDEMEN UUD 1945 - Hasananuddin Hasan (FAKULTAS HUKUM UM PAREPARE, 2017)
The Constitution is the legal basis of state owned by each State. Indonesia as a unitary state in the form of a republic and the State of law is concerned with all aspects of the problem with the applicable law, the constitution in this case the 1945 Constitution as the basis of the state of Indonesia becomes the norm of normality at any time change, Indonesia since 1945 until now has made changes in the amendment form to the 1945 Constitution in 1999-2002, this change is due to the 1945 Constitution or the old order is no longer appropriate with the development at that time. The amendment results provide the legal configuration of law within the State of Indonesian law, and its value: to reduce the power of the State's establishment, to strengthen the legislative body, to promote human rights, to complement State institutions and to improve the 1945 Constitution in terms of literal, grammatical, historical, sociological, socio-historical, futuristic, holistic, thematic to systematic-thematic holistic.